Simulation Training in Penile Implant Surgery: Assessment of Surgical Confidence and Knowledge With Cadaveric Laboratory Training. Issue 4 (24th October 2018) - Lentz, Aaron C.; Rodríguez, Dayron; Davis, Leah G.; Apoj, Michel; Kerfoot, B. Price; Perito, Paul; Henry, Gerard; Jones, LeRoy; Carrion, Rafael; Mulcahy, John J.; Munarriz, Ricardo
Abstract: Introduction: Constraints on surgical resident training (work-hour mandates, shorter training programs, etc.) and availability of expert surgical educators may limit the acquisition of prosthetic surgical skills. As a result, training courses are being conducted to augment the prosthetic surgery learning experience. Aim: To evaluate the impact of a hands-on cadaver-based teaching program on resident procedural knowledge and procedural confidence with placement of a penile prosthesis. Main Outcome Measure: Changes in procedural knowledge and self-confidence following a focused training program on penile prosthetics. Methods: As part of the 2017 Society of Urologic Prosthetic Surgeons and the Sexual Medicine Society of North America Annual Meeting, 31 urology residents participated in a simulation lab in prosthetic urology. The lab included didactic lectures and a hands-on cadaveric laboratory. Participants completed surveys before and after the course. Wilcoxon Signed Rank tests for matched pairs were used to compare respondents' pre- and postcourse knowledge (% questions answered correctly) and confidence ratings. Prior implant experience was assessed. Results: 31 residents participated in this study. The majority of the participants were 4th- (41.9%) and 5th-year residents (38.7%). Participants showed a significant improvement in procedural knowledge test scores (68.8±13.4 vs 74.2 ± 13.0, P < .05) and self-reported increased median surgical confidence levels (4 vs 3, P value < .001) after completion of the cadaveric course. Subgroup analysis demonstrated that residents with prosthetic surgery experience of <10 cases benefited the most. In addition, improvement in surgical confidence levels observed was greater than the improvement in surgical knowledge. The overall cost of the simulation training course was approximately 1, 483 per resident. Conclusion: Simulation training in prosthetic surgery seems to improve surgical confidence and knowledge. Further research is needed to better understand the benefits and limitations of simulation training.